SYSTEMATIC ANALYSIS OF THE RELATIONSHIP BETWEEN CHARACTER ACCENTUATIONS AND ANXIETY LEVELS IN EARLY ADOLESCENCE - Yurchuk, Svitlana (Personality and environmental issues, 2026)
The article considers the fundamental problem of the interaction of static and dynamic properties of the psyche in early adolescence (15–18 years). The relevance is due to the need to reveal the internal mechanisms of emotional maladjustment, where personal anxiety acts not as an autonomous state, but as a function of the characterological profile of the individual. The study is aimed at overcoming the scientific gap between the descriptive characteristics of accentuations and the functional analysis of anxiety reactions in stressful conditions. The aim is to provide theoretical justification and experimental research into the cognitive-affective determination of anxiety states through the prism of typological features of personality character. To collect and analyze empirical data, a comprehensive approach was used, combining the diagnostic method of H. Shmishek's character accentuation types (according to K. Leonhard), the concept of situational and personal anxiety (C. Spielberg, Yu. Khanin) and the provisions on the age sensitivity of early adolescence (A. Lychko). The study is based on a quantitative analysis of the results of the H. Shmishek questionnaire (adaptation of K. Leonhard's concept). The sample demonstrates indicators on 10 scales, where values ​​​​over 18 points are interpreted as pronounced accentuation, and over 21 points - as strong accentuation with a high risk of psychosocial maladjustment. The sample consists of 50 people aged 15 to 18 years. Charles Spielberg's method (adapted by Yuri Khanin), which provides results on two scales: reactive and personal anxiety, where ≥45 is high anxiety, ≤ 30 is low. Statistical processing of the data set was based on descriptive statistics methods (determination of mode and mean) and Pearson correlation analysis to identify interdetermination between the indicators of both methods. During the experimental study, it was found that the sample is characterized by high indicators of hyperthymic (x=18.6) and exalted (x=17.4) accentuations, which creates the prerequisites for a high intensity of emotional response. A statistically significant positive relationship "Anxiety-Exaltation" (r=0.78; p<0.01) was verified, which proves that personal anxiety (x=43.8) in this age period acts as an internal stimulus for affective outbursts. It is proven that exaltation is an "outlet" for accumulated anxiety. A negative correlation was found between hyperthymia and reactive anxiety (r=-0.45), which allows us to interpret hyperthymia as an adaptive mechanism that reduces the subjective significance of stressful events through active social extraversion. The analysis revealed that the level of pedantry (x=7.9) was significantly reduced, which, taking into account high anxiety, indicates a complicated ability of respondents to rationally structure their own emotions and experiences.